2014
DOI: 10.1371/journal.pone.0104626
|View full text |Cite
|
Sign up to set email alerts
|

Attentional Blink Is Hierarchically Modulated by Phonological, Morphological, Semantic and Lexical Connections between Two Chinese Characters

Abstract: The ability to identify the second of two targets (T2) is impaired if that target is presented less than ∼500 ms after the first (T1). This transient deficit is known as attentional blink (AB). Previous studies have suggested that the magnitude of the AB effect can be modulated by manipulating the allocation of attentional resources to T1 or T2. However, few experiments have used Chinese characters and words to explore this phenomenon. The existence of lexical, semantic, phonological and morphological connecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Our results revealed that the first identified character (T1 or T2) increased the probability of identifying the second target (T2 or T1), and such relation priming was mutual for the two targets at very short SOAs in transposed, canonical, and reversible conditions ( Figure 4 ). The performance for canonical words was almost identical across all SOAs, which was consistent with our previous study that involved lexical-semantic priming with two-character compound words ( Cao et al, 2014 ). The similar patterns of results across three word categories indicate that the bidirectional relation priming between T1 and T2 boosts compound word processing across all SOAs and contributes to the elimination of AB.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results revealed that the first identified character (T1 or T2) increased the probability of identifying the second target (T2 or T1), and such relation priming was mutual for the two targets at very short SOAs in transposed, canonical, and reversible conditions ( Figure 4 ). The performance for canonical words was almost identical across all SOAs, which was consistent with our previous study that involved lexical-semantic priming with two-character compound words ( Cao et al, 2014 ). The similar patterns of results across three word categories indicate that the bidirectional relation priming between T1 and T2 boosts compound word processing across all SOAs and contributes to the elimination of AB.…”
Section: Discussionsupporting
confidence: 90%
“…In our previous study, we varied the SOAs and the orthographic, phonological, semantic, and lexical connections between two Chinese characters. We found that AB is hierarchically attenuated in T1–T2 pairs that were related phonologically, morphologically, or semantically, but the effect of AB was absent when T1 and T2 were a two-character compound word ( Cao et al, 2014 ). Thus, priming plays an important role in the hierarchical modulation of AB.…”
Section: Introductionmentioning
confidence: 78%
“…It proposes that the organism has a limited attentional capacity; therefore, within certain time duration, the cognitive resource that is distributed to the current task is naturally limited. This theory emphasizes that the distribution model of cognitive resource in the selective attention process is decided by the perceptual load of the current task (Lavie and Tsal, 1994; Lavie et al, 2004, 2014; Cao et al, 2014; Bobak and Langton, 2015; Tan et al, 2015). In the four experiments in the current study, there was no significant difference in the accuracy rate in the central tasks under either the dual-task or the single-task condition, demonstrating that the peripheral task did not affect the central task.…”
Section: Discussionmentioning
confidence: 99%
“…All participants performed a semantic judgment task and a numerical judgment task (see Figure 1). The semantic judgment task was adapted from the previous fMRI and TMS studies (Binney, Embleton, Jefferies, Parker, & Lambon Ralph, 2010;Cao, Bin, Li, & Yan, 2014;Pobric, Jefferies, & Lambon Ralph, 2007, 2010a, 2010b, 2010cVisser, Jefferies, Embleton, & Lambon Ralph, 2012). In this task, subjects were required to select a target word which is most related in meaning to a probe word from three words.…”
Section: Taskmentioning
confidence: 99%
“…The four words used in each trial were matched for image ability (p = .42), word length (p = .65), and word frequency (p = .98). The numerical judgment task was also adapted from previous studies (Binney et al, 2010;Cao et al, 2014;Pobric et al, 2007;Pobric, Jefferies, & Lambon Ralph, 2010a, 2010b, 2010cVisser et al, 2012). Similar to the semantic judgment task, in each trial, a probe number (e.g., 374) was shown on upper half of the screen and three choice numbers (e.g., 319, 368, and 334) were presented underneath.…”
Section: Taskmentioning
confidence: 99%